Cropping systems and resource-use efficiency - YADAV, R L; PRASAD, KAMTA; GANGWAR, K S; DWIVEDI, B S (The Indian Journal of Agricultural Sciences, 2013)
Cropping system-based approach of research in holistic manner was felt essential only during the last decade tosustain crop-productivity levels attained through high-yielding modern varieties and improved agro-techniques. Efficientcropping systems with respect to biological potential and efficiencies of land, water and nutrients use are discussed andresearch results are updated for ways to increase resource-use efficiencies in prevalent mUltiple cropping systems in thecountry.